Progression of leprosy disability after discharge: is multidrug therapy enough? - Sales, Anna Maria (Trop Med Int Health, 2013)
OBJECTIVE: To evaluate the risk factors related to worsening of physical disabilities after treatment discharge among patients with leprosy administered 12 consecutive monthly doses of multidrug therapy (MDT/WHO). METHODS: Cohort study was carried out at the Leprosy Laboratory in Rio de Janeiro, Brazil. We evaluated patients with multibacillary leprosy treated (MDT/WHO) between 1997 and 2007. The Cox proportional hazards model was used to estimate the relationship between the onset of physical disabilities after release from treatment and epidemiological and clinical characteristics. RESULTS: The total observation time period for the 368 patients was 1 570 person-years (PY), averaging 4.3 years per patient. The overall incidence rate of worsening of disability was 6.5/100 PY. Among those who began treatment with no disability, the incidence rate of physical disability was 4.5/100 PY. Among those who started treatment with Grade 1 or 2 disabilities, the incidence rate of deterioration was 10.5/100 PY. The survival analysis evidenced that when disability grade was 1, the risk was 1.61 (95% CI: 1.02–2.56), when disability was 2, the risk was 2.37 (95% CI 1.35–4.16), and when the number of skin lesions was 15 or more, an HR = 1.97 (95% CI: 1.07–3.63). Patients with neuritis showed a 65% increased risk of worsening of disability (HR = 1.65 [95% CI: 1.08–2.52]). CONCLUSION: Impairment at diagnosis was the main risk factor for neurological worsening after treatment/MDT. Early diagnosis and prompt treatment of reactional episodes remain the main means of preventing physical disabilities.